Efecto de la acupuntura en el punto VB34 en la actividad electromiográfica del músculo erector de la columna - Ramos Alvarado, Martín Josué (Universidad Autónoma Metropolitana, 2013)
The surface electromyography (sEMG) allows registration of the activity generated by skeletal muscle and provides information about normal or pathological state of the peripheral nervous system, motor plate and skeletal muscle. Acupuncture is a medical therapy based on the insertion and manipulation of needles into specific body points. However, studies relating sEMG changes with acupuncture application are limited. The point GB 34 is used alone or in combination with other acupuncture points in the treatment of neuromuscular disorders, especially low back pain. In lower back pain erector spinal muscle is commonly involved. The aim of this paper is to examine the effect of point GB 34 in the sEMG activity of the erector spinal muscle. Materials and methods. We performed a cross-sectional study and experimental in healthy volunteers. Electromyographic activities were compared in three registration periods: Baseline (0 - 60 s), trans (60 - 120 s) and post acupuncture (120 - 300 s); these activities were analyzed by means of the power spectral density of the electromyographic signal with the software Acknowledge v. 4.0. Data are expressed as mean ± SD and statistical test was performed with the T student; paired analysis to compare baseline and posttrans versus acupuncture and unpaired analysis to compare sEMG changes result from stimulation of right versus left GB 34. Results. We studied 15 subjects: 6 (40%) women (33.16 + 9 years old, mean +SD) and 9 (60%) males (37.8 +8 years old, mean +SD). The most remarkable findings of this study are described below. Stimulation of acupuncture VB 34 produced an increase in the amplitude of the signal corresponding to the muscle electromyographic activity erector spinal. The right or left ipsilateral stimulation produced significant increases over baseline levels of studied muscle electromyographic activity in medium and high frequencies of PSD. The comparison of changes in electromyographic activity in ipsilateral muscles tested produced by stimulation of VB 34 point right versus left and evaluated by analyzing the PSD showed no significant difference in the effect of these points. Stimulation of GB 34 produced consistent increases right, but not significant, compared to baseline levels of EMG activity contralateral muscle studied in low and medium frequencies the PSD. Stimulation of GB 34 was left steady increases, compared to baseline values of contralateral muscle electromyographic activity in the three frequencies studied the PSD, but significant only at low frequencies, very remarkable, and high. Comparing the variations in the EMG activity produced by stimulation right versus left of point GB 34 in the contralateral muscles studied showed no significant difference in the effect of these points. This study showed that stimulation of VB 34 produces changes in electromyographic activity of the erector spinal muscle, so ipsilateral and contralateral.; Introducción. La electromiografía de superficie (EMGs), permite el registro de la actividad generada por el músculo estriado y proporciona información acerca del estado normal o patológico del sistema nervioso periférico, de la placa motriz y del músculo esquelético. La acupuntura es una terapéutica médica que trata de la inserción y la manipulación de agujas en puntos corporales específicos. Sin embargo, los estudios de los cambios electromiográficos relacionados con la aplicación de la acupuntura son escasos. El punto VB 34 es empleado sólo o en combinación con otros puntos de acupuntura en el tratamiento de padecimientos neuromusculares, en especial la lumbalgia. Un músculo afectado de manera común en las lumbalgias es el músculo erector de la columna. El objetivo de este trabajo es examinar el efecto del punto VB 34 en la actividad electromiográfica del músculo erector de la columna. Materiales y métodos. Se realizó un estudio de corte transversal y experimental en sujetos voluntarios sanos. Se compararon las actividades electromiográficas en tres periodos de registro: basal (0 – 60 s), trans (60 – 120 s) y pos acupuntura (120 – 300 s) mediante el análisis de la señal electromiográfica densidad del espectro de potencia con el software Acknowledge v. 4.0. Los datos se expresaron como media ± DE y se aplicó la prueba estadística T student con análisis pareado para comparar los valores basales versus los trans y pos acupuntura; y análisis no pareado para comparar los cambios electromiográficos resultado de la estimulación de VB 34 derecho versus VB 34 izquierdo. Resultados. Se estudiaron 15 sujetos: 6 (40%) mujeres (33.16 + 9 años de edad) y 9 (60%) varones (37.8 + 8 años de edad). Los hallazgos más notables de este estudio se describen a continuación. La estimulación con acupuntura de VB 34 produjo un aumento en la amplitud de la señal correspondiente a la actividad electromiográfica del músculo erector de la columna. La estimulación ipsilateral derecha o izquierda produjo aumentos significativos respecto a las cifras basales de actividad electromiográfica del músculo estudiado en las frecuencias media y alta del DEP. La comparación de las variaciones de la actividad electromiográfica en los músculos estudiados ipsilaterales producidas por la estimulación del punto VB 34 derecho versus izquierdo y evaluadas mediante el análisis de la DEP no mostró diferencias significativas en el efecto de estos puntos. La estimulación de VB 34 derecho produjo aumentos constantes, pero no significativos, respecto a las cifras basales de actividad electromiográfica del músculo estudiado contralateral en las frecuencias baja y media del DEP. La estimulación de VB 34 izquierdo produjo aumentos constantes, respecto a las cifras basales de actividad electromiográfica del músculo contralateral estudiado en las tres frecuencias del DEP; pero sólo significativas, en las frecuencias baja, de manera muy notable, y alta. La comparación de las variaciones de la actividad electromiográfica producidas por la estimulación del punto VB 34 derecho versus izquierdo en los músculos estudiados contralaterales no mostró diferencias significativas en el efecto de estos puntos. Este estudio mostró que la estimulación de VB 34 produce modificaciones de la actividad electromiográfica del músculo erector de la columna, de manera ipsilateral y contralateral.